Pengaruh Pemberian Latihan Calf Raises Terhadap Peningkatan Kekuatan Otot Gastrocnemius Pada Pemain Bulutangkis Di Sekolah Bulutangkis Pusaka Putih Sukoharjo - Fitriani, Dewi; , Totok Budi Santoso, S.Fis., MPH; , Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background: Badminton is a sport that is very explosive, involves a unique movement technique and strength in the field. One of the exercises to increase the strength of the gastrocnemius muscle is the calf raises exercise is one way to reduce injuries. Objective: This study aimed to determine the effectiveness of the provision of calf raises exercise for increasing the strength of the gastrocnemius muscle. Methods: This study used a pre-experimental design method with the approach of one group pre test and post test design. The number of samples in this study 12 people, how sampling using purposive sampling method. Of three purposive sampling method, which is used in this research is judgment sampling. Engineering judgment sampling is done when a researcher chooses the members of the sample to adjust to some criteria. As well as using a system of drop out. System drop out if respondents do not exercise regularly will fall/is not used. Results: Data obtained normal distribution, statistical tests using Wilcoxon test to test the hypothesis. And obtained p value: 0.002 or p <0.05, which means there is the effect of calf raises exercise before and after exercise to increase the strength of the gastrocnemius muscle. Conclusion: the effect of calf raises exercise to increase muscle strength gastronemius.